2017
DOI: 10.1155/2017/5176384
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Five Strains of Shiga ToxigenicEscherichia coliin a Sausage Fermentation Model and Subsequent Sensitivity to Stress from Gastric Acid and Intestinal Fluid

Abstract: The ability of foodborne pathogens to exhibit adaptive responses to stressful conditions in foods may enhance their survival when passing through the gastrointestinal system. We aimed to determine whether Escherichia coli surviving stresses encountered during a model dry-fermented sausage (DFS) production process exhibit enhanced tolerance and survival in an in vitro gastrointestinal model. Salami sausage batters spiked with five E. coli isolates, including enterohaemorrhagic E. coli strains isolated from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The stress responses of STEC pathogens, as the results indicated in the present study, might differ when food is introduced in the acid challenges. Rode et al (2017), investigated the survival of STEC strains in a digestion challenge after sausage fermentation and they reported non-O157 isolates had survival patterns similar to that of O157 strains. Miszczycha et al (2014), reported the fate of STEC O157 and O26 during a digestion challenge of contaminated cheeses was dependent on the strain and O26 survived significantly better than O157.…”
Section: Changes In the Populations Of Stec Serogroups And Natural Flora During Frankfurter Storagementioning
confidence: 99%
“…The stress responses of STEC pathogens, as the results indicated in the present study, might differ when food is introduced in the acid challenges. Rode et al (2017), investigated the survival of STEC strains in a digestion challenge after sausage fermentation and they reported non-O157 isolates had survival patterns similar to that of O157 strains. Miszczycha et al (2014), reported the fate of STEC O157 and O26 during a digestion challenge of contaminated cheeses was dependent on the strain and O26 survived significantly better than O157.…”
Section: Changes In the Populations Of Stec Serogroups And Natural Flora During Frankfurter Storagementioning
confidence: 99%